Risk stratification and response to therapy in patients with pulmonary arterial hypertension and comorbidities: a COMPERA analysis - Rosenkranz, Stephan; Pausch, Christine; Coghlan, John G.; Huscher, Doerte; Pittrow, David; Grünig, Ekkehard; Staehler, Gerd; Vizza, Carmine Dario; Gall, Henning; Distler, Oliver; Delcroix, Marion; Ghofrani, Hossain A.; et al. (The journal of heart and lung transplantation, 2023)
Background - A diagnosis of idiopathic pulmonary arterial hypertension (IPAH) is frequently made in elderly patients who present with comorbidities, especially hypertension, coronary heart disease, diabetes mellitus, and obesity. It is unknown to what extent the presence of these comorbidities affects the response to PAH therapies and whether risk stratification predicts outcome in patients with comorbidities. - Methods - We assessed the database of COMPERA, a European pulmonary hypertension registry, to determine changes after initiation of PAH therapy in WHO functional class (FC), 6-minute walking distance (6MWD), brain natriuretic peptide (BNP) or N-terminal fragment of probrain natriuretic peptide (NT-pro-BNP), and mortality risk assessed by a 4-strata model in patients with IPAH and no comorbidities, 1-2 comorbidities and 3-4 comorbidities. - Results - The analysis was based on 1,120 IPAH patients (n = 208 [19%] without comorbidities, n = 641 [57%] with 1-2 comorbidities, and n = 271 [24%] with 3-4 comorbidities). Improvements in FC, 6MWD, BNP/NT-pro-BNP, and mortality risk from baseline to first follow-up were significantly larger in patients with no comorbidities than in patients with comorbidities, while they were not significantly different in patients with 1-2 and 3-4 comorbidities. The 4-strata risk tool predicted survival in patients without comorbidities as well as in patients with 1-2 or 3-4 comorbidities. - Conclusions - Our data suggest that patients with IPAH and comorbidities benefit from PAH medication with improvements in FC, 6MWD, BNP/NT-pro-BNP, and mortality risk, albeit to a lesser extent than patients without comorbidities. The 4-strata risk tool predicted outcome in patients with IPAH irrespective of the presence of comorbidities.